Transparent heat-resistant curling polylactic acid film and preparation method thereof

By blending and granulating and casting of modified zinc oxide whiskers and polylactic acid resin, and stretching and shaping at high temperature, a polylactic acid film with high transparency and excellent heat curling resistance was prepared, solving the problem that the polylactic acid film is prone to deformation and curling at high temperatures.

CN119529342AActive Publication Date: 2025-02-28GUANGDONG GUOKE HAINA NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411692993.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-28
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Polylactic acid film materials are prone to deform and curl under higher temperature conditions, affecting their application.

Method used

By mixing the nucleating agent, modified zinc oxide whiskers with polylactic acid resin evenly, casting and molding after granulation, and stretching and shaping at a preset temperature, a transparent anti-thermal curling polylactic acid film was prepared. Modified zinc oxide whiskers improve surface roughness and functional group content through plasma treatment, and enhance the interface bonding strength with polylactic acid resin.

Benefits of technology

This film product has high transparency and excellent heat curling resistance, which significantly improves the dimensional stability of polylactic acid film in high temperature environments, and solves the problem that the film is prone to deform and curling at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529342A_ABST
    Figure CN119529342A_ABST
Patent Text Reader

Abstract

The invention discloses a transparent heat-resistant curling polylactic acid film and a preparation method thereof, and relates to the technical field of polymer packaging materials. The preparation method provided by the invention comprises the following steps: uniformly mixing a nucleating agent, modified zinc oxide whiskers and polylactic acid resin, and granulating to obtain polylactic acid composite resin master batch; carrying out tape casting on the polylactic acid composite resin master batch to obtain a film blank; stretching the film blank at a preset temperature, and shaping to obtain a polylactic acid film product; the modified zinc oxide whiskers are obtained by performing surface plasma treatment on zinc oxide whiskers. The polylactic acid film product has high transparency and excellent heat curling resistance. The preparation method of the transparent heat-resistant curling polylactic acid film has the advantages of simple process, easily available raw materials, low cost and excellent product performance. The transparent heat-resistant curling polylactic acid film has high transparency and excellent heat-resistant curling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer packaging materials, and in particular to a transparent heat-resistant curled polylactic acid film and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) resin is a biodegradable polyester polymer obtained by polymerization of lactic acid as the main raw material. Polylactic acid is currently the biodegradable polymer material with the largest production capacity and the most extensive application. Polylactic acid can be prepared into products for different purposes through various processing techniques such as injection molding, casting, spinning, etc. In addition to biodegradability, the obtained products also have good biocompatibility, mechanical properties, transparency and texture.

[0003] Since the crystallization speed of polylactic acid is very slow and there is almost no crystallization during the processing and molding process, the obtained products are often amorphous polylactic acid, so its dimensional stability is poor, and the heat deformation temperature is generally only 55-60℃. Due to the residual stress inside the polylactic acid during the processing, especially the film packaging products are prone to curling and other thermal deformation after exceeding the heat deformation temperature, which greatly affects its practical application. Improving the dimensional stability of PLA at higher temperatures is also a research hotspot in the current research on the application of polylactic acid.

[0004] Patent CN102206406A discloses a method for preparing a transparent heat-resistant polylactic acid modified material, which utilizes a chain extender, polymethyl methacrylate-coated modified chitosan whiskers, and a polylactic acid composite material modified by blending phosphite to improve the thermal stability of the polylactic acid system. The polymethyl methacrylate-coated chitosan whiskers used in this method need to be coated with the chitosan whiskers by free radical polymerization initiated by an initiator in an aqueous solution system. The degree of free radical polymerization reaction is relatively intense, and the process is not easy to control. It is easy for polymethacrylic acid to polymerize in the water system to form agglomerates, thereby failing to effectively coat the chitosan whiskers, resulting in an unstable product.

[0005] Patent CN118386581A discloses a high-transmittance biaxially stretched polylactic acid film and its preparation method and application, a method for obtaining a polylactic acid film with high thermal stability by biaxially stretching a three-layer (surface melt, middle layer melt and inner layer melt) polylactic acid film, wherein the three layers of melt in the method are: the surface melt is composed of modified polylactic acid and PBAT; the middle layer melt is composed of hydroxyl-terminated polylactic acid, amino-terminated liquid nitrile rubber, and sebacic acid diphenyl dihydrazide; the inner layer is composed of hydroxyl-terminated polylactic acid and amino-terminated liquid nitrile rubber. Moreover, the surface modified polylactic acid needs to be prepared by aldehyde modification and amino modification in solvents such as dichloromethane. The whole process is relatively cumbersome and complicated, and a large amount of toxic organic solvents such as dichloromethane and chloroform are used.

[0006] Patent CN111548617A discloses a biodegradable polylactic acid material and its preparation method and application, and a method for preparing a polylactic acid film modified by diatom shells, toughening agents and plasticizers. The polylactic acid film prepared by this method improves the toughness and heat resistance of polylactic acid at the same time, but its heat deformation temperature is limited. The heat deformation temperature of polylactic acid in the comparative example is only increased from 53°C to 63°C, which is still far from meeting some use scenarios with high requirements for heat-resistant environment. Summary of the invention

[0007] The technical problem to be solved by the present invention is that the current polylactic acid film material is easily deformed and curled under high temperature conditions.

[0008] In order to solve the above problems, the present invention proposes the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a transparent heat-resistant curled polylactic acid film, comprising the following steps:

[0010] S1, uniformly mixing the nucleating agent, the modified zinc oxide whisker and the polylactic acid resin, and granulating to obtain a polylactic acid composite resin masterbatch;

[0011] S2, tape-casting the polylactic acid composite resin masterbatch to obtain a film body;

[0012] S3, stretching the film blank at a preset temperature and then shaping it to obtain a polylactic acid film product;

[0013] Wherein, the modified zinc oxide whisker is obtained by subjecting zinc oxide whisker to surface plasma treatment.

[0014] A further technical solution is that the zinc oxide whiskers are four-needle zinc oxide whiskers.

[0015] Tetrapod-shaped zinc oxide whisker is a single crystal whisker with a unique three-dimensional structure. Due to its unique three-dimensional tetrapod-shaped structure, it has excellent properties such as high strength, high modulus, wear resistance, antibacterial and antistatic properties, and is widely used as a reinforcing material. However, zinc oxide whiskers have high surface activity and poor interfacial compatibility with low-surface-energy polymer materials. They are easy to agglomerate during blending with resin materials such as polylactic acid, making it difficult to effectively play the role of reinforcing the resin matrix.

[0016] The modified zinc oxide whisker of the present invention adopts plasma treatment technology to carry out surface modification of the zinc oxide whisker, which can effectively increase the surface roughness of the zinc oxide whisker without damaging the integrity of the whisker, and can effectively increase the surface functional group content, thereby improving the interface bonding strength between the zinc oxide whisker and the polylactic acid resin.

[0017] A further technical solution is that the power of the surface plasma treatment is 100-1200W, and the treatment time is 10-120s.

[0018] A further technical solution is that the surface plasma treatment includes air plasma treatment, oxygen plasma treatment, ammonia plasma treatment, and nitrogen plasma treatment.

[0019] A further technical solution is that the size of the whisker needles has a crucial effect on the performance of the polylactic acid resin. In order to provide the polylactic acid film with tensile strength and heat resistance, the needle size of the zinc oxide whiskers of the present invention is 1-50 microns.

[0020] A further technical solution is that in the step S1, the usage ratio of the nucleating agent, the modified zinc oxide whisker and the polylactic acid resin is 0.05-1:0.2-2:100.

[0021] A further technical solution is that the nucleating agent includes one or more of silicon dioxide, calcium carbonate, mica, talc, hydrotalcite, ethylene bisstearamide, sebacic acid diphenyl dihydrazide, suberic acid dibenzohydrazide, zinc citrate, and copper citrate.

[0022] A further technical solution is that in the step S3, the preset temperature is 90-150°C.

[0023] A further technical solution is that in the step S3, the elongation of the film blank is stretched by 1%-100%.

[0024] In a second aspect, the present invention provides a transparent heat-resistant curled polylactic acid film, which is prepared by the preparation method of the transparent heat-resistant curled polylactic acid film described in the first aspect.

[0025] Compared with the prior art, the technical effects achieved by the present invention include:

[0026] The method for preparing a transparent heat-resistant curling polylactic acid film provided by the present invention comprises the following steps: blending and granulating a nucleating agent, a modified zinc oxide whisker and a polylactic acid resin so that each component and the polylactic acid resin are evenly dispersed to obtain a polylactic acid composite resin masterbatch; then the polylactic acid composite resin masterbatch is tape-cast to obtain a film body, and then the final film product is obtained after stretching and inducing crystallization and shaping. The polylactic acid film product has high transparency and excellent heat-resistant curling performance, and effectively solves the problem that the polylactic acid film material is easily deformed and curled under high temperature conditions.

[0027] The preparation method of the transparent heat-resistant curled polylactic acid film of the invention has simple process, readily available raw materials, low cost and excellent product performance.

[0028] The transparent heat-resistant curling polylactic acid film of the invention has high transparency and excellent heat-resistant curling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0030] Figure 1 This is a photo of the zinc oxide whisker used in Example 1 of the present invention.

[0031] Figure 2 This is a photo of the zinc oxide whiskers used in Example 2 of the present invention.

[0032] Figure 3 This is a photo of the film embryo prepared in Example 1 of the present invention.

[0033] Figure 4 This is a photo of the transparent heat-resistant curled polylactic acid film prepared in Example 1 of the present invention.

[0034] Figure 5 This is a graph showing the test results of heat resistance at 90°C of the film embryo and the transparent heat-resistant curled polylactic acid film prepared in Example 1 of the present invention.

[0035] Figure 6 This is a graph showing the results of high temperature resistance testing of the polylactic acid film product obtained in Example 2 of the present invention and the polylactic acid film product obtained in Comparative Example 2. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0038] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0039] Example 1

[0040] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0041] The needle-shaped zinc oxide whiskers (microstructure such as Figure 1 ) was treated with oxygen plasma at a power of 800 W for 30 s to obtain modified zinc oxide whiskers.

[0042] The above-mentioned 1 g of modified zinc oxide whisker, 0.2 g of hydrotalcite, 0.1 g of zinc citrate and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated by a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0043] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0044] The obtained polylactic acid film body with high transparency (such as Figure 3 ), placed in an oven at 110°C and heated to 110°C, then stretched to an elongation of 50%, and quickly taken out after the stretching and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0045] contrast Figure 3 and Figure 4 It can be seen from the photos that the polylactic acid film product prepared in this embodiment still maintains a high transparency after stretching. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 92.7%.

[0046] Temperature resistance test: PLA film products and unstretched film blanks were placed in an oven at 85°C. After 1 hour, the unstretched film blanks were curled and deformed (see Figure 5 The stretched PLA film product was placed in an oven at 85°C for 24 hours without any obvious deformation (see Figure 5 Modified PLA film marked in ).

[0047] The above test results indicate that the transparent heat-resistant curled polylactic acid film provided by the present invention contains modified zinc oxide whiskers, which can greatly improve the dimensional stability of the polylactic acid film in a high temperature environment after being stretched.

[0048] Example 2

[0049] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0050] The needle-shaped zinc oxide whiskers (microstructure such as Figure 2 ) 60Ss was treated with ammonia plasma at a power of 500 W to obtain modified zinc oxide whiskers.

[0051] The above 0.6 g of modified zinc oxide whisker, 0.1 g of silicon dioxide, 0.1 g of talc and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated using a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0052] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0053] The obtained polylactic acid film with high transparency was placed in a 130°C oven and heated to 130°C, then stretched to an elongation of 75%, quickly taken out and quickly cooled to room temperature, and after the stretching was completed, quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0054] The polylactic acid film product obtained in the embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 93.1%.

[0055] Comparative Example 1

[0056] In order to better illustrate the effect of adding zinc oxide whiskers on the final film product, this comparative example is based on the formula of Example 2, except that the modified zinc oxide whiskers are replaced by adding the same mass of silicon dioxide, and the other processes and treatment procedures are the same as those of Example 2. The resulting polylactic acid film product of Comparative Example 1 does not contain zinc oxide whiskers.

[0057] According to the temperature resistance test, the polylactic acid film product obtained in Comparative Example 1 without adding zinc oxide whiskers was obviously curled and deformed after being placed in a 90° C. oven for 1 hour.

[0058] Comparative Example 2

[0059] In order to better illustrate the effect of plasma-treated modified zinc oxide whiskers on the final film product, this comparative example is based on the formula of Example 2, except that the modified zinc oxide whiskers therein are replaced with zinc oxide whiskers that have not been surface plasma treated. The other processes and treatment procedures are the same as those of Example 2, and the resulting comparative example 2 is a polylactic acid film product that has not been surface treated.

[0060] The polylactic acid film product obtained in Example 2 and the polylactic acid film product obtained in Comparative Example 2 were tested for high temperature resistance.

[0061] Test method: The polylactic acid film product obtained in Example 2 and the polylactic acid film product without surface treatment in Comparative Example 2 were placed in a 90°C oven for 2 hours. Figure 6 The results show that the polylactic acid film prepared in Comparative Example 2 using the same process conditions and adding zinc oxide without plasma surface treatment (see Figure 6 The untreated film marked in the middle) was placed at 90°C for 2h and the edge of the film was slightly curled. Its heat-resistant curling performance was improved to a certain extent compared with the polylactic acid film without zinc oxide whiskers added in Comparative Example 1, but the edge was still slightly curled; the transparent heat-resistant curling polylactic acid film product finally obtained in Example 2 of the present invention (see Figure 6 The surface-treated film (marked in the middle) was placed at 90° C. for 2 hours, and no obvious curling occurred in the film as a whole or locally, indicating that the transparent anti-curling polylactic acid film obtained in the embodiment of the present invention has good heat-resistant curling performance.

[0062] Example 3

[0063] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0064] The needle-shaped zinc oxide whiskers with a size of about 50 micrometers were treated by air plasma at a power of 1200 W for 10 seconds to obtain modified zinc oxide whiskers.

[0065] The above 2 g of modified zinc oxide whisker, 0.05 g of talc and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated using a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0066] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0067] The obtained polylactic acid film blank with high transparency was placed in a 150°C oven and heated to 150°C and then stretched to an elongation of 100%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0068] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 90.3%.

[0069] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0070] Example 4

[0071] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0072] The needle-shaped zinc oxide whiskers with a size of about 5 micrometers were treated by nitrogen plasma at a power of 300 W for 120 seconds to obtain modified zinc oxide whiskers.

[0073] The above-mentioned 0.3 g of modified zinc oxide whisker, 0.1 g of talc, 0.5 g of ethylene bisstearamide and 1000 g of polylactic acid were simply stirred and blended, and then extruded and granulated through a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0074] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0075] The obtained polylactic acid film blank with high transparency was placed in a 90°C oven and heated to 90°C and then stretched with an elongation of 10%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0076] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 93.5%.

[0077] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0078] Example 5

[0079] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0080] The needle-shaped zinc oxide whiskers with a size of about 1.2 micrometers were treated with oxygen plasma at a power of 100 W for 120 seconds to obtain modified zinc oxide whiskers.

[0081] The above 0.2 g of modified zinc oxide whisker, 0.5 g of calcium carbonate, 0.5 g of copper citrate and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated through a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0082] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0083] The obtained polylactic acid film blank with high transparency was placed in a 115°C oven and heated to 115°C and then stretched to an elongation of 25%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0084] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 92.1%.

[0085] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0086] Example 6

[0087] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0088] The needle-shaped zinc oxide whiskers with a size of about 20 micrometers were treated by oxygen plasma at a power of 500 W for 60 seconds to obtain modified zinc oxide whiskers.

[0089] The above 0.5 g of modified zinc oxide whisker, 0.1 g of hydrotalcite, 0.1 g of mica and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated using a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0090] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0091] The obtained polylactic acid film blank with high transparency was placed in a 120°C oven and heated to 120°C and then stretched to an elongation of 100%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0092] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 90.3%.

[0093] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0094] Example 7

[0095] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0096] The needle-shaped zinc oxide whiskers with a size of about 10 micrometers were treated with oxygen plasma at a power of 300 W for 100 seconds to obtain modified zinc oxide whiskers.

[0097] The above 0.6 g of modified zinc oxide whisker, 0.1 g of talc, 0.1 g of dibenzoyl hydrazide suberate and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated through a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0098] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0099] The obtained polylactic acid film blank with high transparency was placed in a 105°C oven and heated to 105°C and then stretched to an elongation of 60%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0100] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 92.7%.

[0101] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0102] Example 8

[0103] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0104] The needle-shaped zinc oxide whiskers with a size of about 20 micrometers were treated by oxygen plasma at a power of 800 W for 30 seconds to obtain modified zinc oxide whiskers.

[0105] The above 1.5 g of modified zinc oxide whisker, 0.5 g of talc, 0.25 g of zinc citrate and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated through a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0106] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0107] The obtained polylactic acid film blank with high transparency was placed in a 125°C oven and heated to 125°C and then stretched to an elongation of 50%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50. μm .

[0108] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 90.8%.

[0109] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0110] Example 9

[0111] This embodiment provides a transparent heat-resistant curled polylactic acid film and a preparation method thereof, and the specific steps are as follows:

[0112] The needle-shaped zinc oxide whiskers with a size of about 10 micrometers were treated with oxygen plasma at a power of 1000 W for 100 seconds to obtain modified zinc oxide whiskers.

[0113] The above-mentioned 1.2 g of modified zinc oxide whisker, 0.1 g of silicon dioxide, 0.7 g of suberic acid dibenzoyl hydrazide and 1000 g of polylactic acid resin were simply stirred and blended, and then extruded and granulated through a twin-screw extruder to obtain a uniformly mixed polylactic acid composite resin masterbatch.

[0114] The obtained polylactic acid composite resin masterbatch was cast into a film body with uniform thickness by using a casting machine.

[0115] The obtained polylactic acid film blank with high transparency was placed in a 110°C oven and heated to 110°C and then stretched to an elongation of 80%. After the stretching was completed, it was quickly taken out and quickly cooled to room temperature to obtain a polylactic acid film product with a thickness of about 50 μm .

[0116] The polylactic acid film product obtained in this embodiment still maintains a relatively high transparency after being stretched. According to measurement, the light transmittance of the polylactic acid film product finally obtained reaches 91.1%.

[0117] After the temperature resistance test, the transparent heat-resistant curling polylactic acid film product finally obtained in this embodiment was placed at 90°C for 2 hours, and no obvious curling occurred at the edge, indicating that the transparent curling-resistant polylactic acid film obtained in this embodiment has good heat-resistant curling performance.

[0118] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0119] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a transparent heat-resistant curled polylactic acid film, characterized in that: The following steps are involved: S1, uniformly mixing the nucleating agent, the modified zinc oxide whisker and the polylactic acid resin, and granulating to obtain a polylactic acid composite resin masterbatch; S2, tape-casting the polylactic acid composite resin masterbatch to obtain a film body; S3, stretching the film blank at a preset temperature and then shaping it to obtain a polylactic acid film product; Wherein, the modified zinc oxide whisker is obtained by subjecting zinc oxide whisker to surface plasma treatment.

2. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: In the step S1, the usage ratio of the nucleating agent, the modified zinc oxide whisker and the polylactic acid resin is: 0.05-1:0.2-2:100。 3. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: The nucleating agent includes one or more of silicon dioxide, calcium carbonate, mica, talc, hydrotalcite, ethylene bisstearamide, sebacic acid diphenyl dihydrazide, suberic acid dibenzohydrazide, zinc citrate and copper citrate.

4. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: The zinc oxide whisker is a four-needle zinc oxide whisker.

5. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 4, characterized in that: The needle-shaped body size of the zinc oxide whisker is 1-50 microns.

6. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: The power of the surface plasma treatment is 100-1200W, and the treatment time is 10-120s.

7. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: The surface plasma treatment includes air plasma treatment, oxygen plasma treatment, ammonia plasma treatment, and nitrogen plasma treatment.

8. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: In the step S3, the preset temperature is 90-150°C.

9. The method for preparing a transparent heat-resistant curled polylactic acid film according to claim 1, characterized in that: In the step S3, the film blank is stretched to an elongation of 1%-100%.

10. A transparent heat-resistant curled polylactic acid film, characterized in that: The transparent heat-resistant curled polylactic acid film is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano zinc oxide / polypropylene / polylactic acid composite fiber material and preparing method thereof

    CN101407948A

  • Method for preparing transparent heat-resistance polylactic acid modification material

    CN102206406A

  • Polylactic acid film as well as preparation method and application thereof

    CN117362959A

  • Polylactic acid-based resin composition and polylactic acid-based resin molded product

    JP2011122027A